On-site testing and case management to improve hepatitis C care in drug users: a prospective, longitudinal, multicenter study in the DAA era - Dana Busschots; Rob Bielen; Özgür M. Koc; Leen Heyens; Eefje Dercon; Rita Verrando; Filip Janssens; Luc Van den Bergh; Peter Van Lint; Liesbeth Bruckers; Frederik Nevens; Geert Robaeys (BMC, 2021)
Abstract Background Screening and treatment of hepatitis C virus (HCV) infection in people who use drugs (PWUD) remains insufficient. Reducing the burden of HCV infection in PWUD requires interventions focusing on the different steps of the HCV care cascade. Methods We performed a prospective, multicenter study, evaluating the impact of an HCV care model on the HCV care cascade among PWUD attending an addiction care center in Belgium between 2015 and 2018. Interventions within the care model consisted of pre-test counseling, on-site HCV screening and case management services. A multiple logistic regression model was performed to identify the independent factors influencing the outcomes. Results During the study period, 441 PWUD were registered at the addiction care center, 90% (395/441) were contacted, 88% (349/395) were screened for HCV infection. PWUD were more likely to be screened if they had ever injected drugs (p < .001; AOR 6.411 95% CI 3.464-11.864). In 45% (157/349), the HCV antibody (Ab) test was positive, and in 27% (94/349) HCV RNA was positive. Within the Belgian reimbursement criteria (fibrosis stage ≥ F2), 44% (41/94) were treated. Specialist evaluation at the hospital was lower for PWUD receiving decentralized opioid agonist therapy (p = .005; AOR 0.430 95% CI 0.005-0.380), PWUD with unstable housing in the past 6 months before inclusion (p = .015; AOR 0.035 95% CI 0.002-0.517) or if they were recently incarcerated (p = .001; AOR 0.010 95% CI 0.001-0.164). Conclusions This HCV care model demonstrated high screening, linkage to care, and treatment initiation among PWUD in Belgium. Using the cascade of care to guide interventions is easy and necessary to monitor results. This population needs guidance, not only for screening and treatment initiation but also for the long-term follow-up since one in six had cirrhosis and could develop hepatocellular carcinoma. Further interventions are necessary to increase linkage to care and treatment initiation. Universal access to direct-acting antiviral therapy from 2019 will contribute to achieving HCV elimination in the PWUD population. Trial registration Clinical trial registration details: www.clinicaltrials.gov ( NCT03106194 ).